The Role of Morphological Analyzer and Generator for Tamil Language in Machine Translation Systems - Sheshasaayee, Ananthi; Deepa.V.R, Angela (International Journal of Computer Sciences and Engineering, 2014)
Natural language processing aims to design and build software that will analyze, understand and generate languages that humans use naturally. Machine translation is a very important application in Natural language processing (NLP).Currently, Statistical machine translation plays a predominant role in machine translation of larger vocabulary tasks. Achieving this goal is not an easy task especially when it comes to languages like Tamil which are agglutinative in nature. Deep analysis is needed at the word level to confine the correct meaning of the word from its morphemes and categories.The computational implementation of analysing natural language is done by Morphological analyzer.This paper is a ground work for better understanding of various approaches that are used to develop morphological analyzer and generator of Tamil languages.